Answer:
I did this quickly, so please check carefully.
d/a = -(11/12)
Explanation:
a/(b+c+d)=4/3
3a = 4(b+c+d) [Cross multiply]
3a = 4((b+c)+d) [Note that b and c can be grouped as (b+c)]
---------------------
We can see the second equation also has a (b+c) group. Isolate it to one side:
a/(b+c)=3/5
5a = 3(b+c)
(b+c) = (5a/3)
------------------
Now use this definition of (b+c) in the first equation:
3a = 4((b+c)+d)
3a = 4((5a/3)+d) [Use the new value of (b+c), which is (5a/3)]
3a = 4(5a/3+3d/3)
3a = 4((5a + 3d)/3)
3a = (4/3)(5a + 3d)
3a = (20/3)a + 4d
9/3a = (20/3)a + 4d
-(11/3)a = 4d
4d = -(11/3)a
d = -(11/12)a
d/a = -(11/12)